RELATIONSHIP BETWEEN HOW TO LEARN, MATHEMATIC COMMUNICATION, AND LEARNING FACILITIES WITH RESULTS OF MATHEMATICS STUDENTS IN SMP MUHAMMADIYAH 4 YOGYAKARTA - Desta Senja Nuansa; Uswatun Khasanah (Universitas Ahmad Dahlan, 2017)
Student learning outcomes are determined by many factors. How to learn, mathematical communication and learning tools are several factors related to student learning outcomes. This study aims to determine whether or not there is a positive and significant relationship between learning methods, mathematical communication, and learning tools with mathematics learning outcomes for students of class VIII of SMP Muhammadiyah 4 Yogyakarta odd semester 2016/2017 academic year. The population in this study were eighth-grade students of SMP Muhammadiyah 4 Yogyakarta 2016/2017 academic year, consisting of classes VIIIA, VIIIB, VIIIC, VIIID totaling 104 students. Samples were taken from class VIIIB as a class of research samples with random sampling techniques to the class. Data collection techniques used a questionnaire method to obtain data on learning methods and learning tools, as well as test methods to obtain mathematical communication data and mathematics learning outcomes. Research instrument test: validity test, different power test, and reliability test. Analysis prerequisite tests include normality test, linearity test, and independence test. Data analysis uses product moment analysis and multiple linear regression analysis. The results showed that there was a positive and significant relationship between ways of learning, mathematical communication, and learning facilities with mathematics learning outcomes of VIII grade students of SMP Muhammadiyah 4 Yogyakarta Odd Semester 2016/2017 Academic Year. This was indicated by Fcount Ftable that is 4,692 > 3,05 with R = 0,6252 and R2 = 0,391 with , with SR, SR and SR , SE=, SE and SE .